Non-coding RNA-mediated regulation of seed endosperm development - Wei, Xinqi; Wang, Huanhuan; Zheng, Kaifeng; Han, Shengcheng; Zhang, Fanfan (Frontiers in Plant Science, 2025)
The endosperm, a triploid nutritive tissue in seeds, plays pivotal roles in embryo development, grain yield and quality. Recent advances highlight non-coding RNAs (ncRNAs) as central regulators of endosperm development, which integrate epigenetic, transcriptional, and post-transcriptional mechanisms. Small RNAs (sRNAs), including microRNAs and small interfering RNAs, regulate endosperm cell proliferation, starch biosynthesis, and genomic dosage response by modulating hormonal pathways, metabolic processes, and transposon silencing. Long non-coding RNAs (lncRNAs) contribute to cellularization, nutrient accumulation, and genomic imprinting via chromatin remodeling, gene expression regulation, or interactions with sRNAs. Despite growing evidence of their roles, functional characterization of ncRNAs in endosperm biology remains limited, with many regulatory mechanisms unresolved. This review synthesizes current insights into ncRNA-driven processes governing endosperm development, emphasizing the potential of ncRNAs as targets for crop improvement. Future research should prioritize functional validation of ncRNAs networks and their integration with multi-omics approaches to unlock novel strategies for precision breeding and grain trait optimization.